The synthesis and crystal structure of bis(2-(benzo[d]thiazol-2-yl)-5-methylbenzen-1-ido-κ2C,N)-(N,N′-diethyldithiocarbamato-κ2S,S′)iridium(III), C33H30N3S4Ir - Chen Lianqing; Wu Zhongda; Yang Jing; Zhang Shijuan (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C33H30N3S4Ir, monoclinic, P21/c (no. 14), a = 11.6429(10) Å, b = 10.9111(10) Å, c = 24.234(2) Å, β = 93.2890(10)°, V = 3073.6(5) Å3, Z = 4, Rgt(F) = 0.0198, wRref(F2) = 0.0507, T = 273(2) K.